Pay for Performance : Evaluating Performance Appraisal and Merit Pay - Thériault, Roland (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "Pay for Performance : Evaluating Performance Appraisal and Merit Pay," by G.T. Milkovich and A.K. Wigdor.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z